2016
DOI: 10.1163/15685357-02003004
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Religious Beliefs on Environmental Indicators

Abstract: In this paper, the authors examine whether the more environmental-aggressive attitude of Christianity suggested by Lynn White (1967) could be sustained based on environmental indicators. The religious beliefs were obtained from a World database on religious practices, and the environmental variables from the Environmental Performance Index. Several controlling factors were generated to decouple the influence of religious traditions from other external variables, such as economic wealth or governance. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…(Weaver & Agle, 2002). In this research, in line with some earlier works (Cai & Shi, 2019; Chuvieco, Burgui, & Gallego‐Álvarez, 2016; Leventis et al, 2018; Vitell, 2009), we have opted for the percentage of believers in a specific religion in a country.…”
Section: Research Sample Variables and Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…(Weaver & Agle, 2002). In this research, in line with some earlier works (Cai & Shi, 2019; Chuvieco, Burgui, & Gallego‐Álvarez, 2016; Leventis et al, 2018; Vitell, 2009), we have opted for the percentage of believers in a specific religion in a country.…”
Section: Research Sample Variables and Methodsmentioning
confidence: 88%
“…Given that some previous studies mention the importance of including economic factors (e.g., Chuvieco et al, 2016; Kennedy & Lawton, 1996) that may shape different perspectives, we have included some control variables, such as profitability, size, leverage, and activity sector. To measure profitability, we have used return on assets (ROA); corporate size has been measured through the log of total assets of the company.…”
Section: Research Sample Variables and Methodsmentioning
confidence: 99%
“…This line of inquiry also resulted in mixed findings: whereas some studies found that believers of Eastern religions were more likely to carry out sustainable behaviours and hold more positive environmental views than Western religious followers, Christians in particular [48,62], others found contradicting findings [63,64]. A similar conclusion was found in a global study comparing the environmental performance of countries with different religions, concluding that similar values were found across Eastern and Christian traditions [65].…”
mentioning
confidence: 86%
“…Groups such as Creation Care and Christians for the Mountains have gained national attention for their efforts to limit environmental degradation in Appalachia (Witt, 2016) [31]. However, again, the role of religion remains disputed, as religion in the context of an environmental issue may be reflective of community perspective rather than the cause of a community's environmental stance (Chuvieco et al, 2016) [32].…”
Section: Question 2: "What Is Your Gender? ___ (Classification)"mentioning
confidence: 99%